THE EFFECT OF GIANT FALSE AGAVE FIBER COMPOSITION ON THE DYNAMIC PROPERTIES OF COMPOSITE MATERIALS - Muhammad Hasan Basri (Universitas Negeri Malang, 2026)
Composite is a new material formed from a combination of two or more materials that have mechanical properties stronger than the constituent materials. The development of composite technology is currently moving towards natural composites. One of the natural composites currently being developed and researched is the giant false agave plant fiber composite. This composite is a new material that utilizes giant false agave plant fiber as a reinforcement combined with an epoxy resin matrix with variations of 60%: 40%, 70%: 30%, and 90%: 10%. The use of composite materials in industry still pays attention to the required characteristics, such as mechanical properties and dynamic properties. The purpose of this study is to determine the dynamic characteristics of new materials based on vibration tests using an impact hammer with the Impulse Excitation Technique (IET) method which is evaluated through micro photography and structural morphology analysis. composite materials against variations in epoxy resin based on Electro Scanning Microscopes (SEM) testing. The results of this study indicate that the results of dynamic testing with EMA extraction carried out on Gianf false agave fibrous composite materials obtained dynamic characteristic values including masses of 0.32 g, 1.9 g, 2.3 g respectively, damping ratios of 0.30%, 0.27%, 0.25% respectively, stiffnesses of 32.7 x 10-6 N/m, 26.9 x 10-6 N/m, 57.3 x 10-6 N/m respectively, damping coefficients of 19.4 N.s/m, 60.7 N.s/m, 73.7 N.s/m respectively and natural frequencies of 1602 Hz, 1733 Hz, 1779 Hz respectively, and the second result of micro photo testing, composites with 20% fiber volume have a natural frequency of 6880 Hz, where the frequency is lower when compared to the frequency experienced by composites with fiber volumes of 40% and 60%, namely 8480 Hz and 11200 Hz. The higher the fiber volume, the greater the natural frequency and stiffness produced by a material, but produces less damping.